1999
DOI: 10.1128/jvi.73.11.9303-9313.1999
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Adenovirus Vectors Devoid of All Viral Genes by Recombination between Inverted Repeats

Abstract: Direct or inverse repeated sequences are important functional features of prokaryotic and eukaryotic genomes. Considering the unique mechanism, involving single-stranded genomic intermediates, by which adenovirus (Ad) replicates its genome, we investigated whether repetitive homologous sequences inserted into E1-deleted adenoviral vectors would affect replication of viral DNA. In these studies we found that inverted repeats (IRs) inserted into the E1 region could mediate predictable genomic rearrangements, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Vectors deleted of E1, E2A, E4, and E3 [46,47] and vectors lacking all viral genes have been developed for gene therapy. The latter type of constructs, commonly referred to as gutted vectors, can be propagated only in the presence of helper viruses, which commonly contaminate the vector batches [48]. Furthermore, gutted adenoviral constructs can currently not be propagated to quantities needed for clinical development of vectors destined for mass vaccination.…”
Section: Types Of Adenoviral Vectors: Deletionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vectors deleted of E1, E2A, E4, and E3 [46,47] and vectors lacking all viral genes have been developed for gene therapy. The latter type of constructs, commonly referred to as gutted vectors, can be propagated only in the presence of helper viruses, which commonly contaminate the vector batches [48]. Furthermore, gutted adenoviral constructs can currently not be propagated to quantities needed for clinical development of vectors destined for mass vaccination.…”
Section: Types Of Adenoviral Vectors: Deletionsmentioning
confidence: 99%
“…Alternatively, construction of other serotypes of adenoviral vectors, in which the endogenous E4 ORF6 (which binds to E1B) is replaced by that of AdHu5 virus, may allow for their propagation on available cell lines that provide the E1 of AdHu5 virus in trans [51]. Propagation of adenoviral vectors with additional deletion in either E4 or E2 requires that the deleted genes be provided by the packaging cell lines [46,47] or by a helper virus [48].…”
Section: Types Of Adenoviral Vectors: Deletionsmentioning
confidence: 99%
“…To propagate the helper-dependent genome, the presence of a helper virus that provides the functions required for replication and assembly is required, as production of a complementing cell line has not been possible because of the need for high levels of some virion components and the toxicity of some of these proteins to the cell. The main problem to date is the inability to completely separate virions containing the helper-dependent chromosome from those containing the helper virus genome (Steinwaerder et al, 1999;Sandig et al, 2000). Early strategies that were pursued to reduce helper virus contamination included the use of a helper virus carrying a mutated packaging signal, and minimizing the size of the helper-dependent chromosome compared with that of the helper virus with the hope that the two types of virions could be separated on the basis of their different densities.…”
Section: Helper-dependent Vectorsmentioning
confidence: 99%
“…Previously, we demonstrated that IRs inserted into first-generation Ad vector genomes mediate precise genomic rearrangements resulting in vector genomes devoid of all viral genes that are efficiently packaged into functional Ad capsids (36). We hypothesized that these deleted genomes were formed by intermolecular homologous recombination between the IRs.…”
Section: Generation and Characterization Of Adenovirus-aav Hybrid Vecmentioning
confidence: 99%
“…In addition, this hybrid vector should be devoid of all Ad genes whose expression may cause immunological or toxic side effects. On the way to reach this goal, we utilized our earlier finding that inverted repeat sequences (IRs) inserted into Ad vector genomes mediated predictable genomic rearrangements resulting in vector genomes devoid of all viral genes (36). These genomes (named ⌬Ad.IR) contained only the transgene cassette flanked on both sides by precisely duplicated IRs, Ad packaging signals, and Ad ITRs.…”
mentioning
confidence: 99%